Make it go - Evans, David, 1937-; Williams, Claudette (New York : Dorling Kindersley, 1992)
Uses simple observations and experiments to explore the forces that cause movement.
Includes index.
Booklist
School Library Journal
Horn Book Magazine
1.9
K-3
Keywords: Force and energy -- Experiments -- Juvenile literature; Force and energy -- Experiments; Experiments; Force and energy -- Experiments; Science -- Experiments